Rate and Frequency of Fertilizer Zinc Application on Zn Fractions in Inceptisols of Gujarat, India - Dileep Kumar (Journal of the Indian Society of Soil Science, 2023)
A six year study (2012-18) was carried out to assess the effect of different application rate and frequenciesof zinc (Zn) fertilizer on different forms of Zn in the Inceptisols of Gujarat, India in a maize–wheatcropping system. The efficiency of applied Zn was evaluated in combinations of four different rates (2.5,5.0, 7.5 and 10.0 kg Zn ha-1) and at three different frequencies (first year only, alternate year and everyyear). Additionally, one Zn control plot which received only the recommended dose of fertilizers (RDF)was also included. The experiment was designed in a randomized block design with three replications. Asequential extraction method was adopted to fractionate water-soluble Zn (WS-Zn), exchangeable Zn (EXZn),Zn bound to carbonate (Car-Zn), Zn bound to iron (Fe) and manganese (Mn)-oxide (FeO/MnO-Zn),Zn bound to organic matter (OM-Zn), residual Zn (Res-Zn) and total soil Zn forms. The results showed thatthe continuous application of Zn for six years increased concentrations of all soil Zn fractions irrespectiveof Zn application rate and frequencies. Increasing Zn input increased the percentages of Ex-Zn, Carb-Zn,FeO/MnO-Zn and to soil total Zn, whereas reduced the OM-Zn and Res-Zn fraction. Apparent Zn recoveryefficiency varied with the application rates from 1.46% in 2.5 kg Zn ha-1 applied every year to 0.17% in 10kg Zn ha-1 applied during first year of study in maize crop and from 1.70% in 2.5 kg Zn ha-1 applied everyyear to 0.34% in 10 kg Zn ha-1 applied in the first year only for the wheat crop. Overall the use efficiencyof Zn decreased with increased the rate of Zn application and its frequencies.